1974
DOI: 10.3758/bf03199132
|View full text |Cite
|
Sign up to set email alerts
|

Matching when the number of response alternatives is large

Abstract: Pigeons could choose between five concurrently available response keys, each associated with a different variable-interval schedule of reinforcement. A 2-sec changeover delay was also in effect on each key. In almost all cases, the relative number of responses to a key and the relative time spent at it were nearly equivalent to the relative number of reinforcements it produced. In addition, matching was observed between the relative number of reinforcements at a key and the relative number of changeovers to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
2

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 4 publications
0
21
2
Order By: Relevance
“…This is the question posed in the present research. Previous research has shown that if performance on VI schedules with more than two alternatives is analyzed pairwise, Equation 1 fits well, and there is no effect of the presence, absence, or value of any third alternative on the preference or sensitivity between the other two (Davison & Hunter, 1976;H. Miller & Loveland, 1974;Pliskoff & Brown, 1976).…”
mentioning
confidence: 84%
“…This is the question posed in the present research. Previous research has shown that if performance on VI schedules with more than two alternatives is analyzed pairwise, Equation 1 fits well, and there is no effect of the presence, absence, or value of any third alternative on the preference or sensitivity between the other two (Davison & Hunter, 1976;H. Miller & Loveland, 1974;Pliskoff & Brown, 1976).…”
mentioning
confidence: 84%
“…The optimization theory would also explain why animals march according to "prey size" (length of access to food) when offered two variable-interval schedules that are otherwise identical (Catania, 1963). Although most of the work on matching has involved only two concurrent schedules, Miller and Loveland (1974) have reported matching in a situation where a pigeon is confronted with a choice of five keys, although it is not clear if Shimp's optimization result holds for this more complex environment. Zach and Falls (1976a) studied revisiting of patches (blocks of wood drilled with holes) by ovenbirds in an aviary experiment.…”
Section: -----------------------------------mentioning
confidence: 99%
“…This preservation of equality between distributions of behavior and reinforcement frequency has been demonstrated more recently in diverse experimental settings. These have involved, for example, (1) a continuous type of behavior-standing in place (Baum and Rachlin, 1969); (2) a topographically disparate response-treadle pressing by pigeons (McSweeney, 1975); (3) a large number of response alternatives (Miller and Loveland, 1974;Pliskoff and Brown, 1976); and (4) a naturally occurring aggregate of pigeons (Baum, 1974a). Matching has also been observed in human subjects (see, e.g., Baum, 1975;Schroeder and Holland, 1969).…”
mentioning
confidence: 99%